2009
DOI: 10.1016/j.jstrokecerebrovasdis.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Testing the Superiority of a Postdischarge Care Management Model for Stroke Survivors

Abstract: Objective-To evaluate whether comprehensive post-discharge care management for stroke survivors is superior to organized acute stroke unit care with enhanced discharge planning in improving a profile of health and well-being.Methods-This was a randomized trial of a comprehensive post-discharge care management intervention for ischemic stroke patients with NIH Stroke Scale scores ≥1 discharged from an acute stroke unit. An Advanced Practice Nurse (APN) performed an in-home assessment for the intervention group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
153
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(161 citation statements)
references
References 40 publications
1
153
2
5
Order By: Relevance
“…Thus, focused on clinical spheres and preparatory, prior or subsequent circumstances (terms used in the search: discharge planning; length of stay; after stroke), we can state, just like S 1 (7) , that the best health care results are obtained with more attention dedicated to the hospital-home transition process, with lower probability of re-hospitalization, despite having no direct impact on the QoL of the patient or caregiver. Moreover, S 2 (8) does not present significant differences in the five domains analyzed when comparing two replicable health care models; of these domains, only the one related to knowledge and lifestyle improved with the model, always ensuring discharge planning and follow-up. Another approach used in the studies was the participation of patients in the discharge planning and the relation with a perception of higher or lower HRQoL; S 3 (9) shows that such participation can be positively or negatively perceived.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, focused on clinical spheres and preparatory, prior or subsequent circumstances (terms used in the search: discharge planning; length of stay; after stroke), we can state, just like S 1 (7) , that the best health care results are obtained with more attention dedicated to the hospital-home transition process, with lower probability of re-hospitalization, despite having no direct impact on the QoL of the patient or caregiver. Moreover, S 2 (8) does not present significant differences in the five domains analyzed when comparing two replicable health care models; of these domains, only the one related to knowledge and lifestyle improved with the model, always ensuring discharge planning and follow-up. Another approach used in the studies was the participation of patients in the discharge planning and the relation with a perception of higher or lower HRQoL; S 3 (9) shows that such participation can be positively or negatively perceived.…”
Section: Discussionmentioning
confidence: 89%
“…Conclusion: early attention and care, training, evaluation and follow-up of patients and their families (caregivers) during hospitalization and after discharge, improve the quality of care provided to patients and reduces re-hospitalization. S 2 (8) Considering all domains analyzed related to stroke […], the effect size of the treatment was close to 0 […] for all of them, except for the domain "knowledge and lifestyle", which showed a significant effect resulting from the intervention (p=0.0003). Only the domain "knowledge and lifestyle" improved with the intervention, not demonstrating the superiority of any model ("comprehensive postdischarge care management") in relation to others ("organized acute stroke department care with enhanced discharge planning").…”
Section: mentioning
confidence: 99%
“…Among the twenty-one studies, all but one 31 reported positive findings in at least one category. The authors of five additional studies 25,26,[32][33][34] concluded that their interventions were largely ineffective based on the absence of positive findings on primary outcomes.…”
Section: Study Resultsmentioning
confidence: 99%
“…[ [72] to 380 [55,72]; just under half of trials (11) [58,59,63,67,72,75], three studies chose measures of selfefficacy [53,54,74,79], one study chose a measure of depression as their primary outcome measure [73] and one study chose to measure proactive coping [77].…”
Section: Study Characteristicsmentioning
confidence: 99%